Hindu-Muslim Riots - Lambert, Richard D. (Karachi Oxford University Press, 2013)
A detailed account by an American sociologist of the riots between Muslims and Hindus in Bengal, Bihar, the United Provinces, Punjab, and Bombay that led to the partition of the sub-continent and the establishment of Pakistan and India. Written shortly after the events, it is based on interviews, actual observation of events including the accompaniment of police on efforts at control, official reviews, and detailed newspaper coverage. It is important and has been widely quoted both for its analysis of the sub-continent and for what it contributes to the analysis of urban riots more generally.
Include Appendices, Map, Bibliography, Tables, Glossary and Index.
Keywords: Muslims -- India -- Riots -- Hindus